VARIASI KANDUNGAN KIMIA MINYAK CENDANA (Santalum album Linn) DARI BERBAGAI PROVENANS DI INDONESIA - Liliek Haryjanto; Titis Budi Widowati; Sumardi Sumardi; Ari Fiani; Yayan Hadiyan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
The quality of sandalwood (Santalum album Linn) oil primarily depends on the compound of two major sesquiterpenes (α-santalol and β-santalol). The aim of this research was to identify variation of chemical compounds of sandalwood oil from various provenances. Fifty four samples from 8 provenances and one land race taken from 13th years old sandalwood planted at Gunungkidul, Yogyakarta Indonesia. Sandalwood powder were obtained by drilling tree at 10 cm above the ground horizontally. The samples were extracted with n-hexane solvent. Identification of chemical compounds of this essential oils were conducted by gas chromatography mass spectrometry analysis (GCMS). The GCMS investigation of sandalwood oils showed that variation compounds both among individual within provenance and between provenances were found in 11 individual from 6 provenances. Compounds such as sesquiterpene, monoterpenes, and others, were found in variying amount. The results showed that α-santalol (32.38-78.29%), β-santalol (5.45%-37.83%) were the major compounds with varying quantities of compounds range of epi-β-santalol (5.97-17.16%), P-Menth-2-En-9-OL-Trans (2.87%-8.53%), and α-sinensal (3.83-9.39%).